Exploring Citizenship Unit III: My Clubs and Groups - Joy Jordan (EDIS)
The 4-H Citizenship Project offers you the opportunity to help 4-H members relate all of their 4-H projects and experiences to the world around them. They will learn to care for and share with others through the skills and talents they’ve developed.